Isolation Prevalence of Pulmonary Nontuberculous Mycobacteria in Ontario in 2007 - Mohammed Al Houqani; Frances Jamieson; Pamela Chedore; Mauli Mehta; Kevin May; Theodore K Marras (Canadian Respiratory Journal)
BACKGROUND: The reported prevalence of pulmonary nontuberculous mycobacteria (NTM) infections is increasing.